Application of moderation in determining natural disaster mitigation strategies as inclusive education in elementary school - Kosim Kosim; Syahrizal Stahrizal; I Wayan Gunada (xxxx-xxxx, 2023)
Natural disaster mitigation learning is inclusive education in elementary school. There for, this aims to express the responses and opinions of teachers about the implementation of the disaster mitigation learning model and to improve the ability of teachers in elementary schools. The study was conducted on three schools consist elementary schools in Mataram, Ampenan, and Sembalun in Lombok Island-West Nusa Tenggara-Indonesia. The method of research begins with a presentation of a learning model for natural disaster mitigation such as peer teaching by the research team. After that discussion with moderation technique regarding disaster mitigation learning structure applied in the previous presentation. The results of the study obtained 5 main ideas of strategies about the implementation of the natural disaster mitigation learning model, namely that 1) students must be conditioned to natural disasters in the learning process, 2) teachers must have the correct steps in providing the understanding of natural disasters and in conducting direct demonstrations so that students thoroughly understand, 3) teachers must have knowledge of earthquakes, tsunamis, landslides, floods, hurricanes and volcanoes, 4) teachers provide examples of disaster mitigation learning to students using tools such as videos, disaster mitigation tools, etc, 5) understanding risk, vulnerability, threat and capability of natural disaster. In general conclusion, teachers have to ability to use technology pedagogical and content knowledge strategies for natural disaster mitigation learning.